Numerical Simulation of Gas-Liquid Flow in a Bubble Column by Intermittent Aeration in Newtonian Liquid/Non-Newtonian Liquid. (6th November 2018) - Xipeng, Zheng; Le, Wang; Xiaoxuan, Jia; Wenchuan, Xiang; Shunsheng, Yang
Abstract : The dynamic behaviors of gas-liquid two-phase flow were simulated in a lab-scale intermittent bubble column by Euler-Euler two-fluid model coupled with the PBM (population balance model) using two different liquid phases, i.e., Newtonian fluid (water)/non-Newtonian fluid (activated sludge). When non-Newtonian fluid was used during intermittent aeration, some interesting results were obtained. Two symmetric vortexes existed in the time-averaged flow field; the vertical time-averaged velocity of the liquid phase decreased with increasing anaerobic time; the average gas holdup distribution was like a trapezoid with long upper side and short lower side and affected by the dynamic viscosity of the liquid phase. Compared with non-Newtonian fluid, the use of Newtonian fluid as the liquid phase led to a more complicated time-averaged flow field structure and vertical time-averaged velocity distribution, higher average gas holdup, and the asymmetric column-shaped gas holdup distribution with increasing anaerobic time. For different liquid phases, the instantaneous flow field, instantaneous vertical velocity, and instantaneous gas holdup distribution all periodically changed with anaerobic time; however, different from Newtonian liquid phase, non-Newtonian liquid phase had no periodic oscillating instantaneous horizontal velocity.